Prevalence of mild cognitive impairment subtypes in patients attending a memory outpatient clinic—comparison of two modes of mild cognitive impairment classification. Results of the Vienna Conversion to Dementia Study. Issue 4 (19th November 2012) - Pusswald, Gisela; Moser, Doris; Gleiß, Andreas; Janzek‐Hawlat, Stefan; Auff, Eduard; Dal‐Bianco, Peter; Lehrner, Johann
Abstract: Background: Early detection of dementia is becoming more and more important owing to the advent of pharmacologic treatment. Objective: The goals of this study were to establish prevalence of mild cognitive impairment (MCI) subtypes in an outpatient memory clinic cohort using two different modes of MCI determination. Design: Consecutive patients complaining of cognitive problems who came to the memory outpatient clinic for assessment of a possible cognitive disorder were included in the study. Setting: Academic medical center. Participants: Six hundred eighty consecutive patients complaining about cognitive problems who came to the memory outpatient clinic for assessment of a possible cognitive disorder and fulfilled the inclusion criteria were included in the study. For 676 patients, sufficient data for MCI classification were available. Results: Categorizing MCI patients into MCI subtypes according to the minimum mode of MCI classification revealed the following results: 106 patients (15.7%) were categorized as cognitively healthy, whereas 570 patients (84.3%) met the criteria for MCI. MCI patients were subtyped as amnestic mild cognitive impairment (aMCI) single domain (31 patients; 4.6%), aMCI multiple domain (226 patients; 33.4%), non‐aMCI single domain (125 patients; 18.5%), and non‐aMCI multiple domain (188 patients; 27.8%). Categorizing MCI patients into MCI subtypes according to the mean mode of MCI classification revealed the following results: 409 patients (60.5%) were categorized as cognitively healthy, whereas 267 patients (39.5%) met the criteria for MCI. MCI patients were subtyped as aMCI single domain (47 patients; 6.9%), aMCI multiple domain (57 patients; 8.5%), non‐aMCI single domain (97 patients; 14.3%), and non‐aMCI multiple domain (66 patients; 9.8%). Conclusion: MCI diagnosis frequencies are substantially affected by the criteria used for estimation of MCI. The effect of modifying the presence of impairment on a single cognitive measure versus the presence of impairment on a mean composite score of a certain domain differed considerably, ranging from 39.5% to 84.3%, indicating the importance of the development of guidelines for operationalizing MCI.